Rice Productivity, Zn Biofortification, and Nutrient-Use Efficiency as Influenced by Zn Fertilization Under Conventional Transplanted Rice and the System of Rice Intensification - Choudhary, Anil K.; Sood, Pankaj; Rahi, Shakuntla; Yadav, D. S.; Thakur, O. C.; Siranta, K. R.; Dass, Anchal; Singh, Y. V.; Kumar, Adarsh; Vijayakumar, S.; Bhupenchandra, Ingudam; Dua, V. K.; et al. (Frontiers in Environmental Science, 2022)
The northwestern Himalayas (NWH) in India have low rice productivity (∼2 t ha−1) and quality due to poor crop and nutrient management in predominantly Zn-deficient soils. Hence, a field experimentation in the NWH compared the conventionally transplanted rice (CTR) and the system of rice intensification (SRI) under three nutrient management practices (NMPs), viz., 1) farmers’ fertilization practice, FYM @ 5 t ha−1 + N:P2O5:K2O @ 50:40:20 kg ha−1 (FFP); 2) recommended dose of fertilization, FYM @ 10 t ha−1 + N:P2O5:K2O @ 90:40:40 kg ha−1 (RDF); and 3) RDF + Zn fertilization using ZnSO4 @ 25 kg ha−1 (RDF + Zn). The results revealed that SRI practice harnessed a significantly higher rice yield under different NMPs (6.59–8.69 t ha−1) with ∼1.3–1.4- and ∼3.3–4.3-fold enhancements over the CTR and average rice productivity in NWH, respectively. SRI had the greatest improvement in panicle number hill−1 by ∼2.4 folds over the CTR. RDF + Zn had a significantly higher grain (10.7; 7.9%) and straw yield (28.9; 19.7%) over FFP and RDF, respectively, with significant augmentation of Zn biofortification in grains (11.8%) and Zn uptake (23.9%) over the RDF. SRI also enhanced the Zn concentrations in rice grains and straws by ∼4.0 and 2.7% over CTR with respective increases of 36.9 and 25.9% in Zn uptake. The nutrient harvest index and partial factor productivity of applied nutrients (NPK) had a higher magnitude under SRI and RDF + Zn over their respective counterparts, i.e., CTR and RDF. In addition, SRI had higher AE-Zn, CRE-Zn, and PE-Zn to the tune of 119.6, 63.4, and 34%, respectively, over the CTR. Overall, SRI coupled with RDF + Zn in hybrid rice assumes greater significance in enhancing the rice productivity with better Zn-biofortified grains besides higher nutrient use efficiencies to combat widespread malnutrition and acute Zn deficiencies in humans and livestock in the northwestern Himalayas.